Minutes of the ... annual session of the Synod of New Jersey: Volume 39(1835) (Murray pamphlets., 1835)
1927. Minutes of the one hundred fifth annual session of the Synod of New Jersey. -- 1933. Minutes of the one hundred eleventh annual session of the Synod of New Jersey.